PENGEMBANGAN MODUL KESETIMBANGAN KIMIA BERBASIS GUIDED DISCOVERY LEARNING UNTUK KELAS XI IPA SMA - Oktaria, Weccy (rc-institut, 2019)
This research aims to develop a chemical equilibrium module in guided discovery learning for class XI SMA and determine the level of validity and practicality. This type of research is Research and Development (R & D) with the Plomp model. Plomp model consists of 3 stages, 1) preliminary research, 2) prototyping stage and 3) assessment stage. This module validity test is carried out by 2 chemistry lecturers at FMIPA UNP and 3 chemistry teachers at SMAN 3 Sungai Penuh using validation instruments. Practical tests carried out by 3 chemistry teachers at SMAN 3 Sungai Penuh and 26 XI IPA 1 students from SMAN 3 Sungai Penuh using practice sheets. Instruments of validity and practice sheets are analyzed by the moment formula Kappa (k). The results of the validity analysis with a mean moment score of 0.80 kappa which is a category of high validity. The results of the teacher practice analysis, and the practicality of the students showed that the average kappa (k) score was 0.88, which was a very high practicality category and 0.88 which was also a very high practicality category. The data obtained shows that the chemical equilibrium module based on guided discovery learning for class XI SMA is valid and practical.